Serologic prevalance of salmonella enterica serovar abortusovis infection in sheep and rams from some flocks in the province konya - Zeki Aras; Mehmet Ali Göksu; Uçkun Sait Uçan (Eurasian Journal of Veterinary Sciences)
Salmonella enterica serovar Abortusovis (S. Abortusovis), a Salmonella serovar host-adapted to sheep which causes infectious disease, with abortion as the main symptom. Slow Micro-Agglutination Technique (YMAT) is the reference method for indirect diagnosis of Salmonella enterica Serovar abortusovis. A total of 200 blood serum samples collected from 15 flocks were examined by YMAT to determine the frequency of the disease in the flocks from province Konya. Of the sera, 5 (2.5%) were positive and 195 (97.5%) negative. Sero-positivities for the sheep and rams from province Konya were 3% and 2%, respectively. It is concluded that Salmonella enterica Serovar abortusovis infection is stil endemic in the province Konya.